A targeted proteomic assay for the measurement of plasma proteoforms related to human aging phenotypes. Issue 15 (August 2017) - Semba, Richard D.; Zhang, Pingbo; Zhu, Min; Fabbri, Elisa; Gonzalez‐Freire, Marta; Moaddel, Ruin; Geng‐Spyropoulos, Minghui; Ferrucci, Luigi
Abstract : Circulating polypeptides and proteins have been implicated in reversing or accelerating aging phenotypes, including growth/differentiation factor 8 (GDF8), GDF11, eotaxin, and oxytocin. These proteoforms, which are defined as the protein products arising from a single gene due to alternative splicing and PTMs, have been challenging to study. Both GDF8 and GDF11 have known antagonists such as follistatin (FST), and WAP, Kazal, immunoglobulin, Kunitz, and NTR domain‐containing proteins 1 and 2 (WFIKKN1, WFIKKN2). We developed a novel multiplexed SRM assay using LC‐MS/MS to measure five proteins related to GDF8 and GDF11 signaling, and in addition, eotaxin, and oxytocin. Eighteen peptides consisting of 54 transitions were monitored and validated in pooled human plasma. In 24 adults, the mean (SD) concentrations (ng/mL) were as follows: GDF8 propeptide, 11.0 (2.4); GDF8 mature protein, 25.7 (8.0); GDF11 propeptide, 21.3 (10.9); GDF11 mature protein, 16.5 (12.4); FST, 29.8 (7.1); FST cleavage form FST303, 96.4 (69.2); WFIKKN1, 38.3 (8.3); WFIKKN2, 32.2 (10.5); oxytocin, 1.9 (0.9); and eotaxin, 2.3 (0.5). This novel multiplexed SRM assay should facilitate the study of the relationships of these proteoforms with major aging phenotypes.